Geopolitical Ramifications of India-Space Cooperation: Challenges and Responses from China’s Space Strategy (Journal of Social Sciences Review, 2025)
This article explores the growing space cooperation between India and Russia and  its broader geopolitical impact, particularly in relation to China’s regional ambitions. In the changing landscape of global power politics, space has become a strategic domain where nation seeks technological dominance and strategic advantage. India’s renewed partnership with Russia reflects a calculated move to enhance its space capabilities and counterbalance China’s expanding space influence. Using the theoretical lens of Realism and the Balance of power,this study examines how India-Russia collaboration strengthens multipolarity in space governance and challenges China’s leadership in the Indo-Pacific. The article further analyses China’s strategic responses, including military modernization, regional space alliances, and diplomatic outreach to maintain its position. By investigating this triangular space dynamics, the article highlights how outer space is becoming a critical arena of geopolitical competition, where alliances and rivalries are reshaping both terrestrial and extraterrestrial order.
Keywords: India-Russia Space Cooperation; China’s Space Strategy; Strategic Alliances; Indo-Pacific Security; Space Rivalry in Asia; Asian Security; Space Diplomacy